2019
DOI: 10.3390/ijerph16224453
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Differential Subsidence along the Beijing–Tianjin Intercity Railway with Multiband SAR Data

Abstract: High-speed railways have strict standards of infrastructure deformation and post-construction settlement. The interferometric synthetic aperture radar (InSAR) has the ability to detect ground deformation with a high accuracy and wide coverage and is becoming a useful tool for monitoring railway health. In this study, we analyzed the Beijing–Tianjin Intercity Railway (BTIR) track using InSAR time-series analysis with different data sets. First, by using RADARSAT-2 images, we examined the areas along the BTIR wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The Expectation (Ex) and Entropy (En) methods were proposed in the cloud model, which represents the center of gravity of the cloud and the measure of the fuzziness of the concept, respectively [40,41]. For land subsidence research, Ex and En can be used to represent the overall level and the degree of non-uniformity land subsidence, respectively [42,43]. The high value of Ex means more significant land subsidence, and the high value of En represents more serious inhomogeneity of land subsidence.…”
Section: Expectation and Entropy Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Expectation (Ex) and Entropy (En) methods were proposed in the cloud model, which represents the center of gravity of the cloud and the measure of the fuzziness of the concept, respectively [40,41]. For land subsidence research, Ex and En can be used to represent the overall level and the degree of non-uniformity land subsidence, respectively [42,43]. The high value of Ex means more significant land subsidence, and the high value of En represents more serious inhomogeneity of land subsidence.…”
Section: Expectation and Entropy Methodsmentioning
confidence: 99%
“…In previous studies [42,43], the Expectation and Entropy methods have been used to characterize the spatiotemporal difference of the displacement along subway and railway. In this paper, the Expectation and Entropy methods were used to analyze the overall level and the degree of non-uniform land subsidence in different land use types.…”
Section: Expectation and Entropy Methodsmentioning
confidence: 99%
“…At the same time, Beijing has the largest number of highway overpasses in China. Previous research has mostly focused on regional land subsidence monitoring in Beijing [16][17][18]. Few studies have been conducted on characterizing deformation of transportation lines.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al proved that the Interferometric coherence of X-band SAR data can be well maintained in the monitoring of BTIR [17]. Shi et al analyzed the ground subsidence differences on both sides of the railway by TerraSAR-X data [18]. Zhao et al found that the extraction of groundwater began to slow, but the ground subsidence of the BTIR has not slowed [19].…”
Section: Introductionmentioning
confidence: 99%